Fluctuating body asymmetry in young Polish women in relation to childhood socioeconomic status. Issue 5 (September 2019) - Zurawiecka, Martyna; Marchewka, Justyna; Wronka, Iwona
Abstract: The aim of this study was to analyse the relationship between childhood socioeconomic conditions and body asymmetry in young Polish women. The study measured fluctuating asymmetry (FA), which refers to small random deviations from perfect symmetry in bilaterally paired body structures. Data were obtained from 620 female students aged from 19 to 25 years recruited from Jagiellonian University in Cracow, Poland. The research was carried out in the period from January 2016 to May 2017. A composite fluctuating asymmetry (cFA) of the women was calculated using five bilateral body traits. The lengths and widths of the women's ears, lengths of their 2nd and 4 th digits and wrist widths of the right and left sides of the body were measured twice using standard methodology. The following data were collected in a questionnaire: degree of urbanization of the woman's place of residence during childhood, number of older siblings, parental education and woman's dominant hand. The results showed a tendency for FA to fall with an increase in parental education, and to rise with an increase in number of older siblings. The level of FA was significantly lower in women from rural areas than in those from cities. The results of the study show that FA in early adulthood is significantly associated with socioeconomic status during childhood, and confirm that the level of FA in adulthood may be a good indicator of stress factors in the early stages of development.